2019
DOI: 10.1145/3369828
|View full text |Cite
|
Sign up to set email alerts
|

A Multisensor Person-Centered Approach to Understand the Role of Daily Activities in Job Performance with Organizational Personas

Abstract: Several psychologists posit that performance is not only a function of personality but also of situational contexts, such as day-level activities. Yet in practice, since only personality assessments are used to infer job performance, they provide a limited perspective by ignoring activity. However, multi-modal sensing has the potential to characterize these daily activities. This paper illustrates how empirically measured activity data complements traditional effects of personality to explain a worker's perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…After all, it is much more convenient to deploy a one-time personality assessment. However, Das Swain et al have shown that a worker's day-level activities explain their performance above and beyond their personality [18]. In this work, the authors used activity logs from smartphones, wearables and bluetooth beacons to distinguish its effects from the workers' personality.…”
Section: Moving Beyond Static Personality: Incorporating Temporally-varying Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…After all, it is much more convenient to deploy a one-time personality assessment. However, Das Swain et al have shown that a worker's day-level activities explain their performance above and beyond their personality [18]. In this work, the authors used activity logs from smartphones, wearables and bluetooth beacons to distinguish its effects from the workers' personality.…”
Section: Moving Beyond Static Personality: Incorporating Temporally-varying Activitymentioning
confidence: 99%
“…Particularly, in their dataset, workers who batch their phone use, spend shorter sessions at their desk, and sleep more performed better irrespective of their personality being "resilient" or "undercontrolled" (Figure 1). Not only does an understanding of day-level activity make studies of performance more comprehensive, for certain metrics such as Organizational Citizenship Behavior -often referred to as Contextual Performance -day-level activities explain approximately 50% variance [18].…”
Section: Moving Beyond Static Personality: Incorporating Temporally-varying Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has several limitations about the generalizability of findings, which are similar to many other IMWUT works [13,17,27,29,39] due to the specific region or product investigation. First of all, we only investigated car sharing user behavior in China.…”
Section: Limitations and Future Workmentioning
confidence: 61%
“…We control our models with the same covariates used in matching. We eliminate correlated features using variance inflation factor (threshold = 10) (Das Swain et al 2019, Miles 2014). We also include regularizations (L1, L2) and interaction terms (degree 2) in the regression models.…”
Section: The Effect Of Supportive Interventionsmentioning
confidence: 99%